2012
DOI: 10.1186/1471-2164-13-658
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into strategies used by Xanthomonas albilineans with its reduced artillery to spread within sugarcane xylem vessels

Abstract: BackgroundXanthomonas albilineans causes leaf scald, a lethal disease of sugarcane. X. albilineans exhibits distinctive pathogenic mechanisms, ecology and taxonomy compared to other species of Xanthomonas. For example, this species produces a potent DNA gyrase inhibitor called albicidin that is largely responsible for inducing disease symptoms; its habitat is limited to xylem; and the species exhibits large variability. A first manuscript on the complete genome sequence of the highly pathogenic X. albilineans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 127 publications
9
90
0
1
Order By: Relevance
“…CRISPR I repeats, although present in all strains under study, showed the existence of similar spacers. CRISPR II, which has also been previously reported for X. albilineans (50), X. oryzae pv. oryzae PXO99A, X. oryzae pv.…”
Section: Discussionsupporting
confidence: 74%
“…CRISPR I repeats, although present in all strains under study, showed the existence of similar spacers. CRISPR II, which has also been previously reported for X. albilineans (50), X. oryzae pv. oryzae PXO99A, X. oryzae pv.…”
Section: Discussionsupporting
confidence: 74%
“…Our study revealed the presence of two alleles of cbsA (BXO1/BXO8 type) and one allele (BXO1 type) is replacing the other (BXO8 type) over time. Interestingly, the gene encoding for cbsA has acquired a frameshift mutation in Xoc and hence was reported to be missing in Xoc 35. This suggests the strong selection pressure on cbsA gene in Xoo strains and pathovars.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed‐field gel electrophoresis (PFGE) groups of each clade were indicated following strain assignment by Pieretti et al . (). Pairwise sequence identities were determined using BioEdit v. 7.1.9 (Hall, ).…”
Section: Methodsmentioning
confidence: 97%